Innovation of population administration services based on the sipraja application in sruni village gedangan sub-district Sidoarjo regency - Fatah Yosi Abdillah; Anwar Anwar; Tree Setiawan Pamungkas (Institute of Computer Science (IOCS), 2023)
This study attempts to describe the innovation of population administration services based on the SIPRAJA application for E-KTP and KK services in Sruni Village, Gedangan Sub-District, Sidoarjo Regency. SIPRAJA innovation is described using Rogers' concept of innovation attributes which include Relative Advantage, Compatibility, Complexity, Triability, Observability.The primary data of this research were obtained through interviews and observations. Interviews were conducted with informants who were selected by purposive sampling. While secondary data was obtained through the results of documentation. The data analysis technique used is interactive data analysis from Miles, Huberman, and Saldana. The results of the study show that the SIPRAJA innovation is in accordance with Rogers' innovation attributes, namely the relative advantage shown by the ease of providing E-KTP and KK services using the SIPRAJA application. Compatibility is shown by the conformity between procedures, in terms of facilities and infrastructure, as well as the ability of residents and operators of Sruni Village. Complexity is shown when the application has problems and complexity when uploading documents. Triability is shown from the existence of trials conducted on the operator of Sruni Village. Observability is shown from the information contained in the application as a guide for SIPRAJA users